THE CONSTRUCTION OF CORPORATE FAULT RELATED TO CORPORATE CRIMINAL ACTS IN THE NEW CRIMINAL CODE: IMPLICATIONS AND FORMULATIONS - Joice Soraya; Wahyu Prawesthi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
In the development of modern criminal law, corporate crime has become a primary concern because corporations, as separate legal entities from the individuals within them, are increasingly involved in various widespread legal violations. Therefore, discussions regarding the construction of "corporate fault" in the new Draft Criminal Code (RKUHP) have become crucial to provide legal certainty and justice in handling criminal acts committed by corporations. This research aims to formulate the appropriate formulation in constructing "corporate fault" related to corporate criminal acts in the new Draft Criminal Code (RKUHP), considering the legal, economic, and business implications that may arise. This research uses a normative legal research method with legislative and conceptual approaches. The results of the analysis will be presented in descriptive-analytical form. The research findings indicate that the appropriate formulation in constructing "corporate fault" related to corporate criminal acts in the new RKUHP is by adopting the concept of corporate criminal liability that allows corporations to be held accountable for the actions or omissions of individuals acting on behalf of or for the benefit of the corporation. However, the new RKUHP needs to clearly define the definition of a corporation, criteria and conditions under which a corporation can be held accountable, types of criminal acts and applicable sanctions, as well as a proportional accountability mechanism while still adhering to criminal law principles, best practices from other countries, human rights protection, legal certainty, investment climate, and practical aspects of law enforcement. This formulation should be comprehensive and balanced to provide legal certainty, justice, and support national economic growth by considering legal implications, appropriate law enforcement mechanisms and evidence, legal certainty aspects, investment climate, corporate compliance and risk management, as well as legitimate business continuity.